Reshaping Marketing Science in Wholesaling and Retailing - López-Leyva, Josué Aarón; Murillo-Aviña, Gloria Janeth; Mellink-Méndez, Sialia Karina; Beltrán Rocha, Lucía (My University, 2024)
The lack of knowledge of the Centennial generation's characteristics, particularly their learning styles, affects the B2C buyer's journey efficiency with research offering little insight into their relationship. This interdisciplinary research carries out a cross-sectional statistical analysis of the learning styles of the Centennial generation based on Kolb's theory (related to consumer behavior), intending to influence the design of strategies to improve the B2C buyer's journey efficiency. For this, a survey was carried out on 351 persons. This survey comprises 12 Statements related to Kolb's learning styles theory. As a result, it was found that the Centennial generation has two dominant learning styles, accommodating (LS1) and divergent (LS3). Considering the above, it is concluded that the Centennial generation prefers concrete experiences related to feeling (EL1). In addition, an interdisciplinary discussion is presented to relate the statistical findings to marketing, web design, consumer anthropology, and mathematical analysis disciplines. Finally, some theoretical and practical implications are presented concerning the B2C Centennials-buyer's journey efficiency.
Buyer´s Journey and Kolb's Learning Styles Buyer´s Journey and Kolb's Learning Styles of the Centennials Related to E-Commerce: An Interdisciplinary Consumer Behavior Perspective
Keywords: Kolb's Learning; Centennials; Campus Ensenada